2021
DOI: 10.1002/ecs2.3509
|View full text |Cite
|
Sign up to set email alerts
|

The influence of predators, competitors, and habitat on the use of water sources by a small desert carnivore

Abstract: Free water can influence the ecology of desert species. While the use of free water is influenced by physiological factors (e.g., species-specific water requirements, moisture in forage, temperature), nonphysiological factors, such as habitat characteristics and interspecific interactions, are also important. In fact, for species of concern, interspecific interactions and habitat can be important factors influencing their spatial and temporal use of the landscape and its resources. The kit fox (Vulpes macrotis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Three out of four mesocarnivores in Fort Hood had significantly lower relative abundance than in Santa Cruz (Figure 4), which may indicate suppression in Fort Hood where coyotes have been released and/or released in Santa Cruz where coyotes are suppressed by pumas, although other factors may affect this as well. This pattern of suppression is commonly observed with large canids in before-and-after studies when apex predators are lost (Brook et al, 2012;Kamler et al, 2003;Newsome & Ripple, 2015) and could be due to direct killing or reduced access to resources (Hall et al, 2021;Palomares & Caro, 1999). It is also possible that the higher number of mesocarnivore species in Fort Hood led to higher competition than in Santa Cruz, which could also affect species' relative abundance.…”
Section: Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…Three out of four mesocarnivores in Fort Hood had significantly lower relative abundance than in Santa Cruz (Figure 4), which may indicate suppression in Fort Hood where coyotes have been released and/or released in Santa Cruz where coyotes are suppressed by pumas, although other factors may affect this as well. This pattern of suppression is commonly observed with large canids in before-and-after studies when apex predators are lost (Brook et al, 2012;Kamler et al, 2003;Newsome & Ripple, 2015) and could be due to direct killing or reduced access to resources (Hall et al, 2021;Palomares & Caro, 1999). It is also possible that the higher number of mesocarnivore species in Fort Hood led to higher competition than in Santa Cruz, which could also affect species' relative abundance.…”
Section: Discussionmentioning
confidence: 78%
“…Gray foxes spatially avoided coyotes in Santa Cruz and were the only mesocarnivore to have offset temporal activity from coyotes in Fort Hood. Many studies have found such avoidance between canids (Hall et al, 2021; Kamler et al, 2003; Levi & Wilmers, 2012), and it is possible these effects are stronger within closely related species (i.e., taxonomic families; Prugh & Sivy, 2020) rather than being purely body size based. Taken together, these results partially support our hypotheses of what we would observe if coyotes acted as apex predators in Fort Hood, but they strongly support the mesopredator release hypothesis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations